The Incapability of the Pakistani Legal System in Addressing the Needs of Marginalized Communities: A Focus on Legislation and the Judiciary - Ali Haider; Javed Ahmed; Mohsin Riaz; Syed Faiz UL Hassan (Social Science Review Archives, 2025)
The systematic inability of the Pakistani legal system to meet the demands of marginalized people is examined in this study utilizing a Critical Legal Studies framework, with a particular emphasis on the judiciary and legislation. It investigates the experiences of several marginalized groups, such as socioeconomic, gender, religious, and ethnic minorities, using a qualitative case study methodology. According to the research, the main causes of inequality are discriminatory laws, judicial bias, and obstacles to obtaining justice. It draws attention to the flaws in both the official and informal judicial systems, highlighting the necessity of extensive reforms. The study comes to the conclusion that in order to guarantee fair treatment and protection for Pakistan's most vulnerable groups, community-driven projects, judicial advancements, and improved access to justice are essential.